Teachers' attitudes towards VLE and its relationship with their teaching performance - Farhana Abd Ghani (Kulliyyah of Education, International Islamic University Malaysia, 2018)
Frog Virtual Learning Environment (Frog VLE) has been introduced in Malaysian schools. This is a comparatively new addition in the Malaysian Education System and its implementation had a positive impact on teaching and learning practices. Nonetheless, recent studies on VLE predominantly focuses on teacher and students' readiness and perceptions, and there is limited research focusing on teachers' attitudes towards this technology, especially in primary education. Hence, this present research attempts to discover teachers' attitudes towards their actual use of the Frog VLE platform. Besides, it is aiming to identify the current trend of the VLE's actual use among primary school teachers of Gombak district. Moreover, the study explores the relationship between teachers' attitudes towards Frog VLE, its actual use and its relationship on teachers' teaching performance. In order to conduct the study, a quantitative survey was carried out among the primary school teachers in Gombak District. The researcher had used the stratified sampling technique to choose the participants where 392 respondents have undertaken the survey. Descriptive analysis was used to address the first research question, “What is the current trend of Frog VLE's actual use among primary school teachers in Gombak District?" and the second research question, “To what extent do teachers show their acceptance of Frog VLE in their teaching practices?” whereas Pearson's Product – Moment Correlation test was employed to the third, “Is there any relationship between teachers' attitudes toward Frog VLE's and its actual use?” and the fourth research questions, “Is there any relationship between teachers' actual use of Frog VLE, and their teaching performance?”. The findings of the study show that there is a significant relationship between teachers' attitudes and Frog VLE's actual use as well as the teaching performance. Thus, this study recommends active participation of teachers in utilising the Frog VLE environment in their teaching practice.